For survival of heritage. Multicultural temples of south-eastern Poland – history written in wood - Jan Wrana; Agnieszka Fitta-Spelina (Budownictwo i Architektura, 2015)
South-eastern Poland - the Border region -for centuries was a place of coexistence of cultures, languages and religions. The symbol of multiculturalism and the remains of the temples are among others many faiths – Catholic churches, Orthodox churches, Protestant churches and Jewish synagogues, a large percentage built of wood - especially in rural areas. Once the pride and glory of his followers, now - due to changes in religious structure of the region, often as a result of tragic events - most likely to change destiny or fall into ruin and deteriorate. Their protection and maintenance is necessary not only because of its architectural value, but above all in order to preserve the memory of those who have already passed away.